PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP INTENTION TO USE DENGAN ATTITUDE SEBAGAI VARIABEL INTERVENING (Studi Kasus E-Wallet Di Yogyakarta) - Rosiana Al Sabaah; Heny Welsa; Nonik Kusuma Ningrum (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to determine the effect of Perceived Usefulness, Perceived Ease Of Use, and Attitude, which affects Intention To Use using the Technology Acceptance Mode (TAM) theory. The trend of using E-Wallet as a transaction tool attracts people to use it in their daily transaction activities . In Indonesia, there are many E-Wallet applications, for example such as OVO, Gopay, and Shopeepay, as well as others. This research will discuss customer interest in using E-Wallet. This study uses a type of quantitative research by selecting 170 respondents as research subjects. The results showed that the Perceived Usefulness variable has a positive influence on Attitudude and Intention To Use while Perceived Ease Of Use has a positive effect on Attitude, but Perceived Ease Of Use has no influence on Intention To Use